150 years of Envangelization in Taiwan. A review from personal witness - Velasco, Sergio Arilbal Edward (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

A análise da cultura organizacional escolar através dos seus artefactos - Correia, Ana; Costa, Adelino (Revista do Fórum Português de Administração Educacional,, 2003)

A case study of the English class council of form 5B (Yuet Wah College, Macau school year 1999-2000): towards a participatory and transformative approach in education - Ching, Desiderio (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A common foreign and security policy in Sino-European relations: crosscurents in a changing relationship - Lam, Hon Kei (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

A descriptive study of students' motivation to learn English in Macao - Kuan, Ho Lam (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A financial evaluation study of Espirit Holding Limited - Ng, Chi Wa (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Pepsico Incorporated - Cenon, Susan Gasque (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Bossini International Holdings Limited - Mieiro, Susana Margarida Baptista (University of Saint Joseph, 2006)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Campbell Soup Company - Ho, Pak Ian (University of Saint Joseph, 2007)
Keywords: Campbell Soup Company; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

A financial valuation study of international business machines - Wong Un Ian, Dora (University of Saint Joseph, 2007)
Keywords: International Business Machines (IBM); Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

A financial valuation study of Johnson & Johnson - Kuan, Hei Man (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of McDonald's Corporation - Iao, Sok Mei (University of Saint Joseph, 2007)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Nike, Inc - Kok, Man Fai Morris (University of Saint Joseph, 2007)
Keywords: Nike; Inc; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

A financial valuation study of Starbucks corporation - Lo, Wai Ha (University of Saint Joseph, 2006)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Wal-Mart Stores, Inc - Hun, Weng U. (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial valuation study of Yum! Brands, Inc - Hun, Weng San (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A mathematics curriculum or lower secondary schools in Macau - Wong, Kin Ming (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A participacao does alunos na escola Lin Tchi Fa: um estudo de caso numa escola de lingua veicular portguesa de Macau - Antunes, Francisco Manuel Pelicano (University of Saint Joseph, 2001)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A process-genre approch in curriculum development for lawyers in Macao: a case study - Fernandes, Raquel de Senna (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A social network analysis of teamwork at CPTTM - Tai, Joe (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study of prayer tauht and/or caught: its meaning, practices and applications - Yuen, Celina (University of Saint Joseph, 2008)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

A valuation of the Costco Wholesale corporation - Rato, Ricardo Jorge Parreira (University of Saint Joseph, 2006)
Keywords: Corporations; Costco Wholesale Corporation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

AACM's next step in the development of Macau aviation - Chua, Michael Rainier (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Action research, information technology and chemistry teaching in a Macau secondary school - Tchiang Van Man, Isabel (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Active life: a business plan for an after-school educational center in Macau - Hoi, Vai In (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An analysis of leadership in school - Ao, Wai Ngán (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An analysis of whether collaborative and cooperative work can improve students' reading and writing in English and enhance the development of higher order thinking - Lai, Pak Cheong (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An exploratory study of students' consumption of non‐alcoholic beverages in Nigeria: A qualitative perspective - Gbadamosi, Ayantunji; Olukayode Iwaloye, Ojo; Bamber, David (Nutrition & Food Science, 2009)
Purpose – Given the diversity which exists among various groups of consumers, the purpose of this paper is to explore students' consumption of non‐alcoholic beverages in Nigeria. Design/methodology/approach – Three focus groups and 20 in‐depth interviews were conducted with students in three universities located in Lagos, Nigeria. Findings – Initial findings indicate that these students' consumption of non‐alcoholic beverages is influenced in many ways. Nevertheless, the most striking of these influences are found to be convenience of purchase, along with availability, price, health concerns, and culture/social reasons. Originality/value – The main contribution of the study lies in the relevance of segmentation, targeting, and positioning activities of business organisations in respect of marketing of non‐alcoholic beverages. Based on the findings, the empirical study will serve as a valuable input to marketers in their planning, analysis, and implementation of appropriate marketing strategies to students vis‐à‐vis the highlighted influences on their consumption of this category of food. It will thus serve as a tool for creating competitive advantage in this prevailing volatile business environment.
Publisher: Emerald Group Publishing Limited
Keywords: Consumer behaviour; Nigeria; Non‐alcoholic drinks; Students

An investigation into issues for leadership in culturally diverse schools - Hough, Elayne (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An investigation into the competence-based approach and the person-centered approach for an all-round teaching approach, with reference to the aims of education - Un, Molly (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

As subculturas organizacionais e a avaliação de escolas: genealogia de uma relação conflitiva em estudo de caso - Correia, Ana; Costa, Jorge (2002)

Asian business management: the case of Japan - Tang, Pui San (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Assessment of the factors affecting solid waste management in Macau - Amuno, Solomon (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Assimetrias de Género. Ensino e Liderança Educativa - Correia, Ana (Fundação Manuel Leão, 2009)
Keywords: DLCRE

Attitude towards celebrity brand advertising in Macao - Pinto, José Ferreira (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Burma (Myanmar) and Buddhism: a study in the religious legitimation of goverment - Hta, I. Naw (University of Saint Joseph, 2008)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

Burnout and Service Employees' Willingness to Deliver Quality Service - Humborstad, Sut I W; Humborstad, Bjarte; Whitfield, Richard (Journal of Human Resources in Hospitality & Tourism, 2007)
Employees are vital for enhancing customer satisfaction and loyalty in service organizations because their proactive involvement is an essential part of delivering the services offered. With the recent rapid growth of tourism in the Macau SAR, service employee workloads are clearly increasing, and consequently one would expect that the incidence of job burnout is rising. This study uses the well-known Maslach Burnout Inventory (MBI) to investigate the relationship between service employees' burnout and their willingness to deliver quality services. Self-administered questionnaires from 110 operational staff in three hotels in Macau have been analyzed. The results indicate that job burnout reduces staff's willingness to deliver quality services and that this effect is moderated by individual staff's level of affective organizational commitment, and their perceptions of the extent of organizational and supervisor support provided by the organization. Based on these results, practical managerial strategies to improve service performance are identified.
Publisher: Routledge _eprint: https://doi.org/10.1300/J171v07n01_03
Keywords: Job burnout; affective organizational commitment; perceived organizational support; perceived supervisor support; quality service delivery willingness

Business incubation in Macao: an exploratory case study of MANETIC - Baldinho, Glória; Chan, May; Figueiredo, André; Ip, Shuana; Vong, Cherry (University of Saint Joseph, 2006)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan for Cafe Brazil Coporation, Ltd - Da Silva, António Miguel do Rosário (University of Saint Joseph, 2006)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Career plateau in Macau: an examination of casino frontline staff - Si Tou, Mecia (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Causation in educational research - Morrison, Keith (Routledge, 2009)
OCLC: ocn277086206
Keywords: Causation; Education; Research

“China Wahala”: the Tribulations of Nigerian “Bushfallers” in a Chinese Territory” - Morais, Isabel (Transtext(e)s Transcultures 跨文本跨文化. Journal of Global Cultural Studies, 2009)
Recent scholarly studies and media coverage have primarily focused on China’s increasing presence and sometimes asymmetrical engagement with Africa in tandem with the new trend of Chinese migration to that continent. Yet, the inverse flux of Africans to China and the emergence of African communities in Southern China over the last decades is influencing some areas of the Pearl River Delta Region, and changing the fabric of cities like Guangzhou, Macau and Hong Kong, in a way without precedent. There are representations or exotic descriptions from some mass circulation magazines and newspapers on the infamous Chungking Mansions in Hong Kong or the so-called “Chocolate-city,”an area centered aroundHongqiao, the village-district and Canaan market in the city of Guangzhou, with its arcades and strip malls filled with ethnic businesses and transnational migrants. In Macau, significant concentrations of African population of different origins are also seen in the “Papa pun” commercial center or in downtown areas. Despite many studies devoted to the “ethnoburbs” in other latitudes, only very recently, these entrepreneurial African communities in Mainland China are starting to become worthy of serious scholarly attention. Yet,there is total absence of studies dealing with the presence of more and more African students and the cultural manifestations of African communities well portrayed in the new African cinema, in music produced by Afro-Chinese bands or even singers.Besides a continuing inward flow of transient Africans who come to China for business on a regular basis, a significant number of settler African traders, particularly Nigerians, have already married local Chinese women, set up families, autonomously run their businesses without recourse to Chinese intermediaries, and established a web of informal and formal committees representing their home nations and states, to solve disputes while maintaining personal and business links with Africa. Besides, those emigrant ‘bushfallers’ who are coming to China solely for business purposes, a new form of “silent” migration of Nigerians comprising students from different backgrounds is enrolling in higher education institutions in the Macau Special Administrative Region of China. These students are coming to pursue their studies or to seek a job to pay their student fees at the margin of the PRC scholarship and stipendprograms for visiting African students that were popular in China in the 1960s and mid-1970s as part of CCP’s foreign policy for Third World aiming friendly relations with Africa. Today, these “transnational” Nigerian students are in their own way affirming their identity and difference, in southern China, in particularly in Macau SAR, thanks to their network of multiple interrelations across nation-states from Africa to Asia and to a combination of perseverance, zeal, and gentleness without subservience. Although they have not been targets for the hostility and even violence like the Shanghai incident of July 1979 or the Nanjing protests in December 1988 at Hehai University targeting African students, today these Nigerian students are facing more subtle forms of ethnocentrism and legal discrimination from immigration laws to daily practices, which always try to associate their citizenship to problematic or easy stereotypes of scam or colour. Yet, at the same time, everything seems to indicate that these newcomers are quick adapting and finding new forms of negotiating their social integration in the Chinese local society which in turn is offering more opportunities.This paper is part of a more ambitious project which aims to assess the new forms of migration from Africa to China and from China to Africa as well as their impact and contribution of globalization. First, this paper considers why and how Macau has evolved from a Portuguese outpost where slavery was a an institutionalized commodity to special administrative region of China where a new urban African community, mostly composed by Nigerian students, is in formation due to opportunities and rapid changes occurring in the region in the first years of the twenty-first century, by comparing the new to old African communities of students and business people/migrant workers from former Portuguese colonies (Angola, Cape Verde, São Tomé and Príncipe, Guinea-Bissau, and Mozambique).Finally, borrowing the title from a sequel movie with the same title of the promising New African cinema, the paper focus on the “China Wahala”or the troubles of these Nigerian students through their tales of their experiences of racism(s) and their negotiations and responses which radically contradicts not only the slogans of cultural diversity propagated by the official discourse and tourist channels as these Nigerians are confronted daily with often dramatic situations ranging from indifference and ostracism to exclusion.
1 citations (Crossref) [2022-09-21] Number: 5 Publisher: Transtext(e)s Transcultures 跨文本跨文化

Chinese shoppers' satisfaction towards western style shopping center in Macao - Chung, Chun Kit (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Christianity in Burma / Myanmar - (1600-2007): on the resilience of culture in evangelization - Pha, Tu (University of Saint Joseph, 2008)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

Citizenship and multiculturalism: towards an agenda for education for Macau - Chan, Chi Hou (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Class size, student achievement and pedagogical principles - Noruega, Charlot Francisca Fernandes (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Club Mac incentive travel consultants: a business plan thesis - U, Soi In (University of Saint Joseph, 2006)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

College choice: how students in Macau choose thier higher education institution - Coimbra, Diamantina Luiza do Rosario Sa (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Complexity theory and curriculum reforms in Hong Kong - Morrison, Keith (Pedagogy, Culture & Society, 2003)
21 citations (Crossref) [2022-09-21]

Crticial analysis of the policy and implementation of the environmental protection education of Macao - Chan, Sek Kiu; Li, Titus, Siu Pang; Ma, William (2009)

Culturas docenes nas organizacoes escolares: estudo de caso numa escola portugesa de Macau - Frota, Ana Paula de Rocha Alves (University of Saint Joseph, 2001)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Culturas organizacionais escolares em transicao: estudo de caso numa escola luso oriental - Correia, Ana Maria Cardoso Pires (University of Saint Joseph, 2001)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Customer satisfaction towards Macaowater service - Tam, In I. (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Developing a new perspective on school improvement - Chen, Kim Yone (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Does gender make a difference in English language learning and attainment of secondary school students in Macau: a case study - Leong, On No (University of Saint Joseph, 2005)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Does repeating a year improve performance? The case of teaching English - Morrison, Keith; Ieong On No, Anna (Educational Studies, 2007)
10 citations (Crossref) [2022-09-21]

Dos Santos Albasini, João (1876–1922) - Morais, Isabel (The International Encyclopedia of Revolution and Protest, 2009)
Born in Magule, Mozambique (Portuguese East Africa), João dos Santos Albasini was a mulatto, the leading intellectual in the main center, Lourenço Marques (today, Maputo), the editor of O Africano (The African) founded 1908, and O Brado Africano (The African Voice) founded in 1918, and a champion of worker and African rights. Often characterized as a republican and a moderate, Albasini had a basic education and an appetite for ideas. He was an avid reader of republican theory, syndicalism, and anarchism – all influential in Portugal – and was familiar with a range of radical ideas circulating in the city's thriving café culture.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781405198073.wbierp0473
Keywords: 1800-1899; 1900-1999; Africa; Southern Africa; bibliography; colonialism; comparative history; imperialism; political history

E-connect technology systems - Tai, Chi Chon (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Educational Philosophy and the Challenge of Complexity Theory - Morrison, Keith (Educational Philosophy and Theory, 2008)
89 citations (Crossref) [2022-09-21]

Effects of service quality on satisfaction of mobile phone customers in Macau - Cheong, Kuok Kuan (University of Saint Joseph, 2005)
Keywords: Customer services; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

(Em)powering Timor-Leste: the electricity sector reform - Mineiro, Rui (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Employee retention: an exploratory study in a Macau casino company - U, Kin Lung (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Evergreen energy services ltd - Ho, Kuai Seng (University of Saint Joseph, 2007)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management transition in Singapore - Ho, Pui Man (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Factors affecting the English learning motivation of Chinese secondary students in the Luso-Chinese school of Macau - Ho, Wai Chong (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Financial valuation of caterpillar incorporated - Chu, Un I. (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

First year parenting and infant development: some implications for parenting education - Yan, Son U. (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Foreign Pharmaceutical Companies in China: IPR and Investment - Ribeiro, Paulo Miguel Mateus Simões (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Foreign tourist's perceptions on the world heritage of Macau - Sales, Henrigtte (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Franchising in Macau: context and perspectives - Remédios, Irene Eulógio dos (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Global, regional and local influences in Singaporean firms - Wong, Chao Heong (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Governance of urban planning in Macau - Leong, Fong Peng (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Ideology, Linguistic Capital and the Medium of Instruction in Hong Kong - Morrison, Keith; Lui, Icy (Journal of Multilingual and Multicultural Development, 2000)
55 citations (Crossref) [2022-09-21]

IFT Professional Knowledge and skills retraining programme: an analysis - Kwan, Wai Ha (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Igualdade de oportunidades educativas em contextos multiculturais - Gomes, Armando Geraldo Pelicano (University of Saint Joseph, 2001)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Implementation of empowerment in Chinese high power-distance organizations - Humborstad, Sut I W.; Humborstad, Bjarte; Whitfield, Richard; Perry, Chad (The International Journal of Human Resource Management, 2008)
The importance of empowerment in service industries is recognized by practitioners and scholars in the West but there has been limited investigation of its impact on the willingness of service personnel in a high power-distance culture. This study examines how empowerment can be facilitated in the high power-distance context of China. Regression and path model analysis using a sample of 290 service employees from six 4-star to 5-star hotels in the Macau SAR China indicate that empowerment positively leads to higher service willingness and this relationship is mediated by performance-based rewards, and organizational and supervisor support. These findings have implications for HR managers considering or using empowerment.
Publisher: Routledge _eprint: https://doi.org/10.1080/09585190802110224
Keywords: empowerment; high power-distance culture; organizational support; performance-based rewards; supervisor support; training

Improving Teaching and Learning in Higher Education: Metaphors and Models for Partnership Consultancy - Morrison, Keith (Evaluation & Research in Education, 2003)
3 citations (Crossref) [2022-09-21]

Internet Services in emerging economies: a case study of India - Nadkarni, Sanjay (University of Saint Joseph, 2001)
Keywords: Internet service; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Job satisfaction's impact on turnover: analysis of the factors influencing job satisfaction in relation to turnover during labor shortages of technical employees - Lei, Chi Fai (University of Saint Joseph, 2006)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

John Paul II and the church in China - Wu, Jianhua (University of Saint Joseph, 2008)
Keywords: Faculty of Religious Studies. Religious Studies; Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

Kitchen of the golden temples: indonesian and burmese restaurant - Ho, Pak Kei (University of Saint Joseph, 2006)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Knowledge management in a Macao public sector bureau: a case study - Tai, Kin Ip (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Learning English in Macao - Cheong, Kit U. (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Liderança feminina nas escolas de Macau: uma abordagem exploratória - Correia, Ana; Costa, Jorge (Revista Portuguesa de Investigação Educacional, 2004)
Number: 3

Lotus flowers and plants - Un, Sek Weng (University of Saint Joseph, 2007)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macau school students and stress: an analysis - George, Elsamma (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Management in China: influences and evolution - Silva, Rita Leonardo Diogo da (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management issues in transition in China - Tang, Sut Mei (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management issues in transition within Singapore - Vong, Kwok Wing (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management issues in transition within South Korea - Lee, Pui Sze (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management style in transition: Singapore - Ng, Kai Ieng (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management styles transitions in China - Branco, Ivânio dos Santos (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Measurement of glass transition in native wheat flour by dynamic mechanical thermal analysis (DMTA) - Pereira, Pedro M.; Oliveira, Jorge C. (International Journal of Food Science & Technology, 2000)
This work describes a method to study glass transition on native starch powders, based on dynamical mechanical thermal analysis using compression tests, and was applied to wheat flour (13.5% water content). This method will allow the determination of Tg in native (unprocessed) starchy materials, with minimal disturbance of the natural structures. The influence of the test conditions (heating rate, frequency and strain) on the glass transition measurements was determined using factorial designs. The values of Tg determined as the maxima of the energy dissipation (peaks in E″) of native flour and of freeze-dried pre-gelatinized flour were not statistically different (around 64 °C). The heating rate did not affect the measurements in the range tested (0.25 to 1 °C min−1). An interactive effect of the strain amplitude and the frequency was detected. The significance of this interaction can be caused by differences in mechanical energy dissipation, which would indicate that not only temperature but also the total energy input may affect this transition. Slight effects of phase separation between gluten and starch were found on native flour.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1046/j.1365-2621.2000.00289.x
Keywords: Phase transitions; starch; viscoelastic properties

Measuring and Targeting Internal Conditions for School Effectiveness in the Free State of South Africa - Kgaile, Abraham; Morrison, Keith (Educational Management Administration & Leadership, 2006)
A questionnaire-based methodology for constructing an overall index of school effectiveness is reported, focusing on within-school conditions of schools, which is currently being used in the Free State of South Africa. The article reports the construction and use of a straightforward instrument for measuring the effectiveness of key aspects of the conditions for school effectiveness in the Free State, using a variety of dimensions. It indicates how this instrument can identify where to intervene in improving schools in order to gain the maximum return on investment of time, effort, development activity and support. The instrument provides aggregated and disaggregated data for individual schools, groups of schools and whole districts, both at a single point in time and over time, thereby enabling the most economical and beneficial development to be planned for targeted individual schools and groups of schools. It enables users to identify the key drivers of the internal school conditions for effectiveness, development and change in schools.
2 citations (Crossref) [2022-09-21]

Men and women in employment in Macau: A longitudinal survey of inequality. - Morrison, Keith (Journal of Macau University of Science and Technology, 2009)

Misbehavior in school: problems and solutions - Cheong, Chun Cheng (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Motivation as a key factor in the learning of English as a second language in Macau - Chiang, In Wa (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

O conflito na escola: analise da emergencia, desenvolvimento e efeitos do conflito na comunidade escolar - Da silva, Maria Isabel Tavares Candeias (University of Saint Joseph, 2001)
Keywords: Schools; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Offshore solution: Macau competitiveness as an offshore jurisdiction - Kolesnikova, Viktoria (University of Saint Joseph, 2004)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Online travel agency Visit2Macau.com - Xavier, Elisa Maria (University of Saint Joseph, 2006)
Keywords: Theses and Dissertations Master of Business Administration (MBA); Tourism; Travel agents; University of Saint Joseph

Organizational change and the application of the theoretical perspective of complexity - Schmitt, Stacy Kathleen (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Paradox Lost: Toward a Robust Test of the Chinese Learner - Morrison, Keith (Education Journal, 2006)
This article suggests that attempts to date to unravel the paradox of the Chinese learner are incomplete and inadequately modeled, and that the complexities of the paradox have not yet been fittingly operationalized or alternative explanations of research data investigated. It contends that attempts either to state or to unravel the paradox are chimerical, as they risk oversimplifying a complex phenomenon, the extent and nature of which are insufficiently understood to date. The article argues that investigating the phenomenon of Chinese learners' strong performance in international measures of achievement requires researchers to operate more rigorously in their search for alternative and multiple explanations of results in terms of causality, sampling, and representing heterogeneity. Several explanations of data on the paradox are presented, and alternative explanations which might be more usefully explored are provided. The article also questions the extent to which research on the Chinese learner, with a search for a unitary set of characteristics, is not, itself, prey to totalizing, collectivist ideologies cast in unrealistic meta-narratives. Recommendations are made for further research.

Parents, students and secondary schools in Macao - Tchiang, Van Man (University of Saint Joseph, 2009)
Macao, a developing city, has been undergoing rapid and significant changes economically, culturally, and socially, partly as a consequence of the changes to the economy brought about by the gaming and tourism industry. Changes in Macao have had a major impact on its schools. Parents have a significant impact on students in school, and Macao’s secondary schools are having to handle a range of challenges and problems brought by students and their parents, many of these as a result of the changes in the wider society of Macao. The response of many schools to the challenges faced is limited, and they understate and under-use the important role played by more developed forms of parental involvement in schools. This study examines the nature, scope and extent of the problems that secondary schools in Macao are having to handle from parents and students, how the schools are handling them, and what needs to be done in order to address the problems and handle them more effectively. Through a large scale survey, interviews and a small scale questionnaire, the thesis identifies key problems facing the schools from students and parents, and it reveals that many of Macao’s secondary schools are ill-equipped to handle these, and there are many signs that the problems are becoming more acute. The thesis finds that negative parental behavior has had a stronger effect on students than positive parental behavior, and it finds that there are several reasons why the schools, in their present state, cannot address these matters effectively. A significant gap is found between what the schools indicate they should be doing and what they are actually doing to address increased parental involvement in order to impact positively on Macao’s students. Recommendations are made for intervention and action
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Pedagogy in higher education - Morrison, Keith (Chinese Cross Currents, 2005)

Perceptions on the surge ogf the youth employees in the boom of gaming industry: the opportunities & threats within and the messages revealed - Lei, Pui Lun (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Perspectives on extra-curricular activities in a secondary school: a survey - Lai, Ka Lon (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Pricing bullish underlying linked securities - Ho, Choi San (University of Saint Joseph, 2006)
Keywords: Bullish underlying linked securities; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Randomised Controlled Trials for Evidence-based Education: Some Problems in Judging 'What Works' - Morrison, Keith (Evaluation & Research in Education, 2001)
58 citations (Crossref) [2022-09-21]

Research in learning using technology - WebCT - Yuen, Fun Lin (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Research Methods in Education - Cohen, Louis; Manion, Lawrence; Morrison, Keith (Routledge, 2007)

Retention factors for I.T. professionals in Macao - Lei, Sok Chi (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

School inspection in small states and territories: an overview and case study of Macau - Morrison, Keith (Compare: A Journal of Comparative and International Education, 2009)
5 citations (Crossref) [2022-09-21]

School leadership and complexity theory - Morrison, Keith (Routledge/Falmer, 2002)
Keywords: Complex organizations; Educational leadership; School management and organization

Selection of low swelling materials for protein adsorption from white wines - Sarmento, Miguel R.; Oliveira, Jorge C.; Boulton, Roger B. (International Journal of Food Science & Technology, 2000)
The protein adsorption capacity of different materials was evaluated to assess their potential efficacy as alternative adsorbents for the removal of proteins from wines, with the purpose of finding suitable low-swelling materials that could be used in a percolated bed. The adsorbents tested were thermally treated sodium bentonite, low-swelling adsorbing clays, ion exchange resins and other protein adsorbents (silica gel, hydroxyapatite and alumina). The materials were evaluated by analysing both the capacity to stabilize untreated white wines, according to a heat test, and by characterizing the adsorption isotherms of bovine serum albumin (BSA) in a model wine (water, ethanol and K-bitartrate). Breakthrough curves in a packed bed were determined experimentally for some materials, showing the influence of the adsorption isotherm shape. Some ion-exchange resins showed a favourable behaviour and have good potential as alternative adsorbents.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1046/j.1365-2621.2000.00340.x
Keywords: Bentonite; percolated beds; sorption isotherms; wine stability

Sensitive educational research in small states and territories: the case of Macau - Morrison, Keith (Compare: A Journal of Comparative and International Education, 2006)
15 citations (Crossref) [2022-09-21]

Service quality of the tax department: a case study of Macau Finance Service Bureau - Tam, Si Weng (University of Saint Joseph, 2007)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Simplicity and Complexity in Contemporary School Leadership: A Response to Grace - Morrison, Keith (British Journal of Educational Studies, 2001)
0 citations (Crossref) [2022-09-21]

Smallpox Vaccinations and the Portuguese in Macao - Morais, Isabel (Review of Culture, 2006)

South Korean management system: transition and transformation - Mak, King Kuoh (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Staffingpros: your trusted source for temporary staff - Choi, Ka I. (University of Saint Joseph, 2007)
Keywords: Business planning; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Structuration theory, habitus and complexity theory: elective affinities or old wine in new bottles? - Morrison, Keith (British Journal of Sociology of Education, 2005)
36 citations (Crossref) [2022-09-21]

Student councils and citizenship eduation: Principles and practices - Tang, Sut Leong (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Study on the management transition in India - Wong, Wai Nap (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Suicide prevention in schools: are Macau's teachers prepared? - Días, Javier Suárez; Morrison, Keith (Macau Inter-University Institute, 2005)
Keywords: China Macau (Special Administrative Region); Prevention; Students; Suicidal behavior; Suicide; Teenagers

Suicide prevention in schools: are Macau's teachers prepared? - Diaz, Javier Suarez (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teacher stress in the Macau workplace - Garcia, Alejandro Salcedo (Inter-University Institute of Macau, 2008)

Teachers stress in the workplace in Macau: an investigation - Chan, Chao Hou (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teaching geometry with the use of Wai Fai Leng's computer program - Chong, Hio Meng (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Testing to Destruction: A problem in a small state - Morrison, Keith; Joan, Tang Fun Hei (Assessment in Education: Principles, Policy & Practice, 2002)
21 citations (Crossref) [2022-09-21]

The Chinese Diaspora in Mozambique - Morais, Isabel (Singapore: The Chinese Heritage Centre Bulletin, 2005)

The efficacy of art therapy: a comparative study of primary school children in Macau - Vai, Man Kei (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

The hospitality industry: a sustainable environment - Martins, Nadia Cristina Baldinho (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The impact of compensation package and organizational culture on job satisfaction and organizational commitment - Choi Kam Ha (University of Saint Joseph, 2006)
Keywords: Compensation management; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The impact of compensation package and organizational culture on job satisfaction and organizational commitment - Choi, Kam Ha (University of Saint Joseph, 2006)
Keywords: Compensation management; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The implementation of the theory of multiple intelligences in the primary section of a school in Macau - Vong Ka I, Catherine (Macau Inter-University Institute, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Introduction of Smallpox Vaccinations in the Pearl River Delta Region - Morais, Isabel (200th Anniversary of Smallpox Vaccines in the Pearl River Delta. Volume 1, 2007)

The invention of colonial Macau in Smirnoff's Paintings (1944-1945) - Lei, Seng U. (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The management in transition - Japan - Iao, Sao Fong (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The poverty of curriculum theory: a critique of Wraga and Hlebowitsh - Morrison, Keith R. B. (Journal of Curriculum Studies, 2004)
16 citations (Crossref) [2022-09-21]

The study of Chinese students pursiong education abroad: culture and learning - Au, Oi Kei (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The use of multimedia in primary teaching: a case study - Lam, Szui Lui (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

To increase forms 1 and 2 students' motivation for English learning in a school in Macau - Chan, Pui San (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Toward an educational agenda for Macau at the start of the new millennium - Morrison, Keith (China Perspectives, 2003)

Undergraduate students in part‐time employment in China - Tam Oi I, Betty; Morrison, Keith (Educational Studies, 2005)
13 citations (Crossref) [2022-09-21]

Understading parental involvement from a socio-cultural perspective - Ao, Sio Heng (Macau Inter-University Institute, 2003)
Keywords: Parent-teacher relationship; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Urban design study for the waterfront area in NAPE: architects perceptions and cultural alternatives - Ma, Sarah (University of Saint Joseph, 2008)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Urban traffic network management - Melo, Anacleto S. Cunha (University of Saint Joseph, 2003)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Use of CALMS to enrich learning in introductory programming courses - Thota, Neena (Proceedings of the 17th International Conference …, 2009)
Use of CALMS to enrich learning in introductory programming courses

Using Mupad to introduce the concept of curve sketching of one variable in high school mathematics - Maung Aung Thinn (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Using MyPad to introduce the concept of function of one variable in high school mathematics - Ng, Wa Loi (University of Saint Joseph, 2001)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Using technology to introduce the concept of differentiation and its applications in high school mathematics - MuPad case study - Wong, Pui Man (University of Saint Joseph, 2001)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Using technology to introduce trigonometry topics in high school mathematics: MuPad case study - Lee, Ion Kei (University of Saint Joseph, 2001)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Using technology to introduce trigonometry topics in high school mathenatics - MuPad case study - Lee, Ion Kei (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Valuation of International Game Technology - Ho, Sao Kun (University of Saint Joseph, 2007)
Keywords: International Game Technology; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

Yeuk Sin Fong 藥膳坊 keeping you healthy naturally - Chan, Hoi Ian (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph